Tactics of environmental NGOs in influencing public policy in Malaysia - Mohd, Rusli; Cheh, Kenny Sonn Lee (Universiti Putra Malaysia Press, 1999)
Environmental non-governmental organizations (NGOs) in Malaysia can influence public policymaking through several political tactics. This study surveyed and compared the tactics used by three selected NGOs, namely, the Sahabat A1am Malaysia (SAM), the Malaysian Nature Society (MNS) and the World Wide Fund for Nature (WWF), Malaysia. The Automobile Association of Malaysia (AAM) was conveniently selected as the control group. Data and information were gathered through face-to-face interview technique with the chief executive officers of the respective organizations or their representative using a structured questionnaire. The findings reveal that the environmental NGOs are different from the AAM in their choice of tactics of influencing public policy. The former prefer to use direct tactics in influencing policy decisions. Tactics such as conducting and presenting research results, presenting personal viewpoints, lobbying and contacting officials, are often used compared to tactics like letter-writing and telegram campaigns, grassroots lobbying, drafting legislation or organizing conferences. Among the NGOs, the MNS has been the most tactical in the sense that it has used more tactics, both direct and indirect, more often than the SAM or the WWF. The MNS is also the most resourceful of the NGOs and this probably explains its capacity to employ more political tactics. Future studies should use a bigger sample as well as investigate the effectiveness of the various tactics used.